DOI: 10.22215/etd/2014-10440
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Sex, Gender Identity, and Power on Faculty-Graduate Student Relational Mentoring and its Association with Student Psychological Health

Abstract: Evidence suggests that university student psychological health problems may be increasing, and graduate students may be at increased risk for problems such as depression relative to the general population. The limited extant research has identified a correlation between relational mentoring characterized by mutual authenticity, engagement, and empowerment, and female undergraduate student psychological health.The current research fills gaps in the mentoring and feminist psychological literatures by examining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 111 publications
(296 reference statements)
0
3
0
Order By: Relevance
“…Peluso et al found that the academic advisor relationship played a role in protecting the mental health of experimental psychology students in Canada 10. Gottschall also showed a significant association between a harmonious mentoring relationship (RHI-M subscale) and decreased depressive symptoms among Canadian graduate students 66. In addition, Lunsford suggested that mentoring by doctoral advisors correlated with student outcomes, including satisfaction and academic production 37…”
Section: Discussionmentioning
confidence: 99%
“…Peluso et al found that the academic advisor relationship played a role in protecting the mental health of experimental psychology students in Canada 10. Gottschall also showed a significant association between a harmonious mentoring relationship (RHI-M subscale) and decreased depressive symptoms among Canadian graduate students 66. In addition, Lunsford suggested that mentoring by doctoral advisors correlated with student outcomes, including satisfaction and academic production 37…”
Section: Discussionmentioning
confidence: 99%
“…In unpublished data, 27 it is suggested that women display more feminine traits (authentic, engaged, etc), and thus, these traits can better guide the development of the mentoring relationship. Our sample population was predominately female; thus, this could provide some context to our findings; that is, female athletic training students want their mentors and preceptors to exhibit what is commonly referred to as sexspecific traits.…”
Section: Discussionmentioning
confidence: 99%
“…). In the graduate context, Gottshall () found significant correlation between mentoring and positive psychological health, as indicated by decreased depressive symptoms, increased self‐esteem, and life satisfaction while McMillan‐Roberts () established that faculty mentors helped doctoral students develop a scholar‐practitioner identity. Looking specifically at meaningful academic relationships between master's students and professors, Schwartz and Holloway () found evidence of The Five Good Things (Miller ), as both students and professors reported increased energy, boosts in sense of worth, increased understanding, the ability to keep moving in their work, and a desire for more connection.…”
Section: Education As Relational Practicementioning
confidence: 99%